Potential activities to improve primary care prescribing of antibiotics across Africa - Chigome, Audrey; Ramdas, Nishana; Campbell, Stephen M.; Gajdács, Márió; Sefah, Israel Abebrese; Hango, Ester; Massele, Amos; Godman, Brian; Meyer, Johanna C. (Frontiers in Tropical Diseases, 2025)
There are considerable concerns with antimicrobial resistance (AMR) across Africa, enhanced by the inappropriate prescribing of antibiotics in ambulatory care. This includes prescribing for self-limiting conditions and Watch antibiotics. Inappropriate prescribing is enhanced by concerns with ambulatory care prescribers’ knowledge of antibiotics, including their perceived effectiveness for self-limiting conditions, AMR, and antimicrobial stewardship programs (ASPs). Appropriate education of prescribers, including surrounding the AWaRe (Access, Watch, and Reserve) system and guidance, which recommends the prescribing of antibiotics with less resistance potential, alongside introducing ASPs in ambulatory care, can help address these concerns. This will increasingly include instigating agreed quality indicators, and their monitoring, surrounding the AWaRe system and guidance. Improved surveillance of local resistance patterns can help with appropriately updating antibiotic prescribing guidance, including revising the AWaRe guidance based on local resistance patterns. Additional financing is also needed to help attain national goals.